Males can adjust offspring sex ratio in an adaptive fashion through different mechanisms. (16th February 2021) - Douhard, Mathieu; Geffroy, Benjamin
Abstract: Sex allocation research has primarily focused on offspring sex‐ratio adjustment by mothers. Yet, fathers also benefit from producing more of the sex with greater fitness returns. Here, we review the state‐of‐the art in the study of male‐driven sex allocation and, counter to the current paradigm, we propose that males can adaptively influence offspring sex ratio through a wide variety of mechanisms. This includes differential production and motility of X‐ versus Y‐bearing sperms in mammals, variation in seminal fluid composition in haplo‐diploid invertebrates, and epigenetic mechanisms in some fish and lizards exhibiting environmental sex determination. Conflicts of interest between mothers and fathers over offspring sex ratios can emerge, although many more studies are needed in this area. While many studies of sex allocation have focused on adaptive explanations with little attention to mechanisms, and vice versa, the integration of these two topics is essential for understanding male‐driven sex allocation. Abstract : Maternal control over offspring sex ratios has constituted the major research paradigm for research on sex allocation. Yet, fathers also benefit from producing more of the sex with greater fitness returns. We discuss the multiple potential mechanisms by which males may adaptively influence offspring sex ratio.